Investigating the Emergence of Digital Platforms for Listening Learning Proficiency - Fitria, Tira Nur (Al-Lisan: Jurnal Bahasa, 2021)
This study investigates the use of any platforms in English language teaching and learning, especially in listening skills. This research design is qualitative. From the result, it shows that some technologies available both online or offline include applications or platforms that provide many choices for listening to English, they are. 1) Music platform. These platforms can be found in PlayStore, such as Joox and Spotify recommends songs for listening skills. 2) Youtube channel. Many YouTube channels for learning English listening skills include 1) Voice of America (VOA), BBC Learning English, Learn English with TV Series, English with Lucy, and Oxford Online English. 3) Podcasts. Both BBC (British Broadcasting Corporation) and VoA (Voice of America). These Podcasts offer listening skills. The other podcasts are “The English We Speak, Podcast in English, Better at English, Luke’s English Podcast, Espresso English Podcast, Anchor FM” etc. 4) Websites that are pretty representative in practicing the listening skills such as Sound English, ESL-Lab, English listening, Ello, learn English British Council, Daily ESL, Story Nory, Story Line, which can be accessed. Learning English through several applications above can be an alternative for students in practicing and improving their English listening skills. Listening exercises can be carried out by using interesting listening strategies when learning English. It depends on the teachers/lecturers who teach listening subjects and the students who learn English materials.